PENGEMBANGAN MODUL PEMBELAJARAN PAI BERBASIS KURIKULUM 2013 DI KELAS V SD NEGERI 21 BATUBASA, TANAH DATAR - Susanti, Riri (Graduate Program Magister Manajemen Pendidikan, 2017)
The problem in this research was the learning of PAI in SD Negeri 21 Batubasa was teacherâs center and limited of teaching materials. This study aimed at developing the PAI learning module based on the 2013 curriculum on understanding Allahs Messangers, being simple life and Ikhlas were valid, practical, and effective. This research was a development research using 4-D model (definition, design, development and dissemination). Based on the results, the PAI learning module was very valid with an average of 3.65 based on validator assessment. The module was considered very practical with an average 3.92 based on teacherâs ratings and average 3.85 based on studentâs ratings. The effectiveness of the module on students learning motivation was in the active category with the average 94.10 and the students learning activity in the active category with the average 92. The studentâs learning outcomes above the Minimum Standard Criteria with an average 85.50. It can be concluded that the PAI learning module developed was valid, practical, and effective.